Weathering processes and dating of soil profiles from São Paulo State, Brazil, by U-isotopes disequilibria - Bonotto, Daniel Marcos [UNESP]; Jiménez-Rueda, Jairo Roberto [UNESP]; Fagundes, Isabella Cruz [UNESP]; Filho, Carlos Roberto Alves Fonseca [UNESP] (Elsevier, 2017)
This study reports the use of the U-series radionuclides 238U and 234U for dating two soil profiles. The soil horizons developed over sandstones from Tatuí and Pirambóia formations at the Paraná sedimentary basin, São Paulo State, Brazil. Chemical data in conjunction with the 234U/238U activity ratios (AR's) of the soil horizons allowed investigating the U-isotopes mobility in the shallow oxidizing environment. Kaolinization and laterization processes are taking place in the profiles sampled, as they are especially common in regions characterized by a wet and dry tropical climate and a water table that is close to the surface. These processes are implied by inverse significant correlations between silica and iron in both soil profiles. Iron oxides were also very important to retain uranium in the two sites investigated, helping on the understanding of the weathering processes acting there. 238U and its progeny 234U permitted evaluating the processes of physical and chemical alteration, allowing the suggestion of a possible timescale corresponding to the Middle Pleistocene for the development of the more superficial soil horizons.
Keywords: Dating; Paraná sedimentary basin; Soil profiles; Uranium isotopes; Weathering processes